Digest: The phylogenetic distance effect: Understanding parasite host switching*. (29th May 2019) - Foster, Charles S. P.
Abstract: Host–parasite relationships are often cited as classic examples of coevolution, but parasites are also able to switch hosts. Is the distribution of parasites across a phylogeny affected by the phylogenetic distance between potential hosts? Engelstädter and Fortuna (2019) provide evidence that the success of host switches is linked to phylogenetic distance between potential hosts, as well as the diversification rate and shape of host phylogenetic trees.